Effectiveness of progestogens to improve perinatal outcome in twin pregnancies: an individual participant data meta‐analysis. (22nd August 2014) - Schuit, E; Stock, S; Rode, L; Rouse, DJ; Lim, AC; Norman, JE; Nassar, AH; Serra, V; Combs, CA; Vayssiere, C; Aboulghar, MM; Wood, S; et al.
<x xml:space="preserve">Abstract</x> Background In twin pregnancies, the rates of adverse perinatal outcome and subsequent long‐term morbidity are substantial, and mainly result from preterm birth (PTB). Objectives To assess the effectiveness of progestogen treatment in the prevention of neonatal morbidity or PTB in twin pregnancies using individual participant data meta‐analysis (IPDMA). Search strategy We searched international scientific databases, trial registration websites, and references of identified articles. Selection criteria Randomised clinical trials (RCTs) of 17–hydroxyprogesterone caproate (17Pc) or vaginally administered natural progesterone, compared with placebo or no treatment. Data collection and analysis Investigators of identified RCTs were asked to share their IPD. The primary outcome was a composite of perinatal mortality and severe neonatal morbidity. Prespecified subgroup analyses were performed for chorionicity, cervical length, and prior spontaneous PTB. Main results Thirteen trials included 3768 women and their 7536 babies. Neither 17Pc nor vaginal progesterone reduced the incidence of adverse perinatal outcome (17Pc relative risk, RR 1.1; 95% confidence interval, 95% CI 0.97–1.4, vaginal progesterone RR 0.97; 95% CI 0.77–1.2). In a subgroup of women with a cervical length of ≤25 mm, vaginal progesterone reduced adverse perinatal outcome when cervical length was measured at randomisation (15/56 versus 22/60; RR 0.57; 95% CI 0.47–0.70) or before 24 weeks of gestation (14/52 versus 21/56; RR 0.56; 95% CI 0.42–0.75). Author's conclusions In unselected women with an uncomplicated twin gestation, treatment with progestogens (intramuscular 17Pc or vaginal natural progesterone) does not improve perinatal outcome. Vaginal progesterone may be effective in the reduction of adverse perinatal outcome in women with a cervical length of ≤25 mm; however, further research is warranted to confirm this finding.